Welsh and diversity: Welsh drag queens and their perspective on the all-Welsh Rule - Gralak, Oliwier; Szczuczko, Katarzyna; Szłapiński, Kacper (Studia Celtica Posnaniensia, 2025)
The purpose of this paper is to analyse the perspectives of Welsh-speaking drag performers regarding the National Eisteddfod and the All-Welsh Rule. We collected data from the participants using qualitative research methods by asking the performers about their opinion on strategies employed for linguistic revitalisation of Welsh, i.e. the National Eisteddfod of Wales and the All-Welsh Rule. The results of this study reveal that while the Eisteddfod is recognized for its role in preserving the Welsh language and culture, the All-Welsh Rule is viewed with more complexity. The participants acknowledge the Rule’s protective function, but also consider it to be too restrictive and point to a need for its reevaluation, thus providing the option for more artists to express their Welsh identity and perspectives within the Eisteddfod. This reveals a tension between preserving linguistic purity and fostering cultural diversity, particularly from the perspective of a minority within a minority. We show that the aforementioned opinions are to some extent parallel to the views of post-war period Welsh performers. We also argue that the notions of contemporary diversity and flexible bilingualism, as reflected in the opinions of modern drag performers, are at odds with the preserving function of the All-Welsh Rule. The results suggest a need for reevaluation of the All-Welsh Rule to better accommodate diverse Welsh identities and encourage broader engagement with the language.